Prognostic factors after resection of colorectal liver metastases following preoperative second-line chemotherapy: Impact of RAS mutations. Issue 9 (September 2016) - Passot, G.; Chun, Y.S.; Kopetz, S.E.; Overman, M.J.; Conrad, C.; Aloia, T.A.; Vauthey, J.-N.
Abstract: Background: After resection of colorectal liver metastases (CLM), RAS mutations are associated with modest survival benefit and second-line chemotherapy confers limited hope for cure. Objective: To evaluate the impact of RAS mutation after second-line chemotherapy for patients undergoing potentially curative liver resection for CLM. Methods: Among 1357 patients operated for CLM between January 2005 and November 2014, patients with known RAS mutational status were identified. Outcomes after second-line chemotherapy were analyzed by RAS status. Results: Among 635 patients undergoing resection of CLM, 46 received second-line chemotherapy before resection, including 14 patients (30%) with RAS mutations. Patients who received second-line chemotherapy had significantly larger and greater number of liver metastases and were more likely to undergo major hepatectomy. Median overall (OS) and recurrence free survival (RFS) were significantly worse among patients requiring second-line chemotherapy (OS: 44.4 vs. 61.1 months, p = 0.021; RFS: 7.3 vs. 12.0 months, p = 0.001). Among patients undergoing liver resection after second-line chemotherapy, RAS mutations were associated with worse median OS and RFS (OS: 35.2 vs. 60.7 months, p = 0.038; RFS: 3.6 vs. 8.3 months, p = 0.015). RAS mutation was the only independent factor associated with OS and RFS. All patients with RAS mutations recurred within 18 months. Among patients with RAS wild-type tumors, the receipt of second-line chemotherapy did not affect OS (p = 0.493). Conclusion: Among patients undergoing resection of CLM after second-line chemotherapy, RAS mutational status is an independent predictor of survival and outweighs other factors to select patients for liver resection.